Analysis and improvement of the CS-based fair exchange protocol - SUN Yan-bin1; GU Li-ze1; SUN Yan3; QING Si-han4; YANG Yi-xian1; CHEN Guang-hui1 (Tongxin xuebao)
Through analysis,the perfect concurrent signature（CS）based fair exchange protocol did not satisfy the prop-erty of the abuse-freeness if both parties were honest.Before releasing the secret information（keystone）,anyone could identify who was the real signer when two parties had exchanged their two ambiguous signatures and relative data items.Then,an improved perfect concurrent signature-based fair exchange protocol was presented which overcame the flaw of the previous scheme and realized the property of the abuse-freeness.Meanwhile,the improved scheme also remains the properties of the previous perfect concurrent signature-based fair exchange protocol,such as fairness,non-repudiation and simple efficiency,and only needs four messages between two parties.